Lexical Wealth in basic education students (high school level) of Lima - Quesada Murillo, María Rosario (2001)
It is tried to determine if significant differences exist in the lexical wealth in function of the school grade and of the type of educational, state center or matter. With a sample of 2956 students to those that it was evaluated with the Test of Wealth and of Lexical Precision built by André King (1962). The data were analyzed by means of the factorial analysis of variance for the individual effect and cocktail and the Analysis of Variance of a Factor for design multigroup. You concludes that both hypotheses are confirmed. That is to say that so much the origin school like the grade of studies cause significant differences.